THE PLASMA MEMBRANE CALCIUM ATPASE 4 SPECIFIC INHIBITOR AURINTRICARBOXYLIC ACID ENHANCES VEGF-INDUCED ANGIOGENESIS. (21st November 2014) - Kurusamy, S; Baggott, RR; López-Maderuelo, MD; Kannappan, V; Escolano, A; Oller, J; Little, R; Dunmore, SJ; Oceandy, D; Cartwright, EJ; Wang, W; Neyses, L; et al.
Abstract : Angiogenesis, the formation of new capillaries from pre-existing ones, is a biological process essential for successful embryonic development, organ growth and tissue repair. Excessive or insufficient growth of blood vessels, due to de-regulation of this process, plays a major role in the pathophysiology of several human diseases. The pro-angiogenic factor Vascular Endothelial Growth Factor (VEGF) has been identified as a crucial regulator of both physiological and pathological angiogenesis. VEGF activates the calcineurin/Nuclear Factor of Activated T-cells (NFAT) signalling pathway which is a critical mediator of angiogenesis. Our group has recently identified a novel role for the plasma membrane calcium ATPase 4 (PMCA4) as a negative regulator of VEGF-dependent angiogenesis. The small molecule Aurintricarboxylic acid (ATA) has been characterised as a selective inhibitor of PMCA4. We hypothesise that ATA-mediated inhibition of PMCA4 in endothelial cells will enhance VEGF-driven angiogenesis. Consistent with this hypothesis, we demonstrate in this work that inhibition of PMCA4 by treatment with ATA increases calcineurin/NFAT activity and the expression of the NFAT-dependent, pro-angiogenic protein RCAN1.4 in VEGF-stimulated HUVEC. Moreover, ATA treatment significantly enhanced endothelial cell migration and tubular morphogenesis in response to VEGF-stimulation. Interestingly, incubation of HUVEC with ATA had no effect on the cell viability or Erk1/2 phosphorylation (activation) status of VEGF-stimulated cells. Our results show a novel role for the PMCA4 specific inhibitor ATA as a stimulator of VEGF-induced angiogenesis. Thus, ATA might lead to the design of new therapeutic strategies to improve blood vessel formation in diseases associated with insufficient angiogenesis.